Moodle, digital board dan video conference: Inovasi media pembelajaran Bahasa Inggris selama emergency remote teaching di masa pandemi Covid-19 - Lina Septianasari (JINoP (Jurnal Inovasi Pembelajaran), 2022)
Innovation in the use of learning media amid an Emergency Remote Teaching (ERT) is indispensable, especially in teaching English as a foreign language. This study aims to document learning innovations carried out by English Lecturers and investigate students’ perspectives regarding learning innovations carried out by their classroom lecturers during ERT. Statistical quantitative and qualitative approaches were used in the research design of this study. Purposive sampling combined with questionnaires and interviews as instruments to collect data. The data were analyzed by using LISREL software supported with a descriptive qualitative approach to calculate statistical data from the questionnaire and to describe data from interviews. The findings indicate that the LMS combined with digital boards and video conference platforms have received quite a positive response from students in terms of material, self-efficacy, and usability. The innovations made by lecturers in integrating learning media can help the lecturers to maintain the achievement of learning activities during ERT.